Landscape-scale benefits of protected areas for tropical biodiversity - Brodie, JF; Mohd-Azlan, J; Chen, C; Wearn, OR; Deith, MCM; Ball, JGC; Slade, EM; Burslem, DFRP; Teoh, SW; Williams, PJ; Nguyen, A; Moore, JH; et al. (Springer Nature, 2023)
The United Nations recently agreed to major expansions of global protected areas (PAs) to slow biodiversity declines. However, although reserves often reduce habitat loss, their efficacy at preserving animal diversity and their influence on biodiversity in surrounding unprotected areas remain unclear. Unregulated hunting can empty PAs of large animals6, illegal tree felling can degrade habitat quality, and parks can simply displace disturbances such as logging and hunting to unprotected areas of the landscape (a phenomenon called leakage). Alternatively, well-functioning PAs could enhance animal diversity within reserves as well as in nearby unprotected sites (an effect called spillover). Here we test whether PAs across mega-diverse Southeast Asia contribute to vertebrate conservation inside and outside their boundaries. Reserves increased all facets of bird diversity. Large reserves were also associated with substantially enhanced mammal diversity in the adjacent unprotected landscape. Rather than PAs generating leakage that deteriorated ecological conditions elsewhere, our results are consistent with PAs inducing spillover that benefits biodiversity in surrounding areas. These findings support the United Nations goal of achieving 30% PA coverage by 2030 by demonstrating that PAs are associated with higher vertebrate diversity both inside their boundaries and in the broader landscape.